Artificial Intelligence dalam Pendidikan: Implikasi Pemanfaatan ChatGPT Terhadap Kualitas Pembelajaran dan Etika Akademik - Hegar Harini; Arbiana Putri; Herlina; Nurhasanah; Nor Khakim (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implications of ChatGPT utilization on learning quality and academic ethics in the context of modern education. The method used is a literature review with a qualitative approach and descriptive analysis of 31 selected articles from a total of 50 sources obtained through Google Scholar within the period 1977–2026. Data analysis techniques involving data reduction, data presentation and drawing conclusions. The results show that the use of ChatGPT contributes to improved learning efficiency, conceptual understanding, and flexibility in the learning process. On the other hand, there are risks of technology dependency, potential decline in critical thinking skills, and increasing violations of academic ethics such as plagiarism. The discussion also highlights the need to strengthen digital literacy, develop authentic assessment models, and establish clear institutional policies to optimize the use of this technology. The use of ChatGPT in education requires a balance between technological innovation and the strengthening of ethical values in order to provide sustainable benefits. This study has limitations as it is based solely on a literature review of 31 articles; consequently, it does not fully represent the development of ChatGPT’s use in education. Further research is recommended to develop empirical studies, strengthen digital literacy and authentic assessment, and formulate policies that balance technological innovation and academic ethics